The establishment of the non-indigenous cyclopoid copepod Oithona davisae in Hamsilos Bay-Sinop, Southern Black Sea, Turkey - Zeynep Hasançavuşoğlu; Tuba Terbiyik Kurt; Funda Üstün (Aquatic Sciences and Engineering)
Hamsilos Bay, which is located within the first–degree natural protection area, is one of the most important regions on the southern Black Sea coast. Moreover, many fish species utilize this area for breeding and rearing activities. Small copepod Oithona davisae has been encountered in the Black Sea for two decades and spread rapidly the overall Black Sea, and become an important component in the pelagic ecosystem of the Black Sea. In this respect, the present study aims to characterize the distribution and abundance of Oithona davisae in Hamsilos Bay about environmental variables. Zooplankton samples were collected monthly from seven stations from July 2015 to June 2016 by using a plankton net with a mesh size of 112 μm and a diameter mouth opening of 50 cm. O. davisae was observed during the whole sampling period and was the dominant species from July 2015 to December 2015. The highest mean abundance of this species was recorded in September 2015 (3533.33 ind. m–3). However, the lowest mean abundance was observed between January 2016 (170.68 ind. m–3) and May 2016 (0.24 ind. m–3). Copepodites 5–4 were predominant in the O. davisae population in all months and all stations. Adult copepods and their copepodites 5–4 were more abundant between July 2015 and December 2015, whereas the abundance of copepodites 3–1 was maximum between September 2015 and December 2015. The abundance of O. davisae was highly correlated with chlorophyll-α and physiochemical variables (temperature, dissolved oxygen, and salinity). In conclusion, this species, which is known to be distributed only in the autumn conditions in close areas, extended its temporal distribution and prevailed in the copepod communities during warmer periods. This could be attributed to the acclimatization success of this species in Hamsilos Bay ecosystems.